Gender Perspective on Child Custody Decisions and Enforcement Problems: An Analysis of Decision Number 566/Pdt.G/2021/PA.Prg - Fajriany Jabbar; Sudirman L; Fikri (Universitas Muhammadiyah Palu, 2023)
The hadanah regulation in the Compilation of Islamic Law (KHI) explains that children who are not yet mumayyiz are under the custody of their mother. Even though custody rights in Decision Number 566/Pdt.G/2021/PA.Prg is determined as stipulated in the KHI: the husband (reconvention defendant) is reluctant to carry out the contents of the quo decision, which results in one of the children being under his care. This is an anomaly in the general view regarding the dichotomy of men's and women's roles. Using a socio-legal approach, this research seeks to avoid the reductionist character that simplifies hadanah disputes into binary categories between compliance and non-compliance with legal provisions and judge's decisions, as well as placing the custody issue into the ongoing social context. Using gender theory and maqasid sharia, this research will dissect the judge's considerations in Decision Number 566/Pdt.G/2021/PA.Prg and their relationship to non-compliance with the quo decision. Based on gender theory, the meaning is that the quo dispute was born simultaneously as awareness of women's involvement in earning a living and of men's participation in caregiving. In its considerations, the assembly was trapped in the social construct of gender roles. The husband's disobedience can be understood as an implication of being disconnected from the judge's considerations from the ongoing social context, where the patriarchal family system, characterized by a dichotomous model of gender roles, is experiencing fragility. Meanwhile, from the analysis of maqasid sharia, it was found that the unequal distribution of happiness (maslahah) desired by maqasid sharia gives rise to a sense of injustice. The logical consequence is that the party who feels burdened with